Advanced engineering economics - Park, Chan S.; Sharp-Bette, Gunter (New York : J. Wiley, 1990)
This book is divided into four parts: Basic concepts and techniques in economic analysis; Deterministic analysis; Stochastic; and Special topics in engineering economic analysis.
Keywords: Economics; Engineering; Engineering economy